PENERAPAN MODEL RAIS-MR3 DALAM TATA KELOLA KEUANGAN DESA DI DESA SIPODECENG - Dahlia Dahlia; Ahmad Mustanir; Haeruddin Syarifuddin; Muhammad Rais Rahmat Razak; Rasdiana Mustapa (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
Village financial management faces challenges of transparency, accountability, and equitable distribution of development benefits despite being regulated in Permendagri No. 20 of 2018. This study aims to analyze the financial management of Sipodeceng Village based on the Rais-MR3 Model. This study uses a qualitative approach with descriptive methods using interviews, observations, and documentation, and is analyzed using NVivo. The results show: (1) the Management dimension has followed formal procedures but community participation is limited; (2) the Regulation dimension has an adequate legal basis but information disclosure is not yet optimal; (3) the Responsibility dimension shows that the division of tasks among officials is running well but social accountability is not yet evenly distributed; (4) the Result dimension has a positive impact on infrastructure but the equitable distribution of benefits still needs to be improved. The financial governance of Sipodeceng Village is in a compliance-based condition that requires strengthening transparency, community participation, and equitable development to achieve good governance. Practical implications include strengthening the capacity of officials through technical training, digitizing the village financial information system, and improving mechanisms for public participation in budget planning and oversight.